Blood flag : a Paul Madriani novel - Martini, Steve, 1946- (2016)
Defending a client accused of mercy-killing her father, attorney Paul Madriani is drawn into a treacherous conspiracy involving the victim's former unit from World War II and a feared Nazi relic
Keywords: Madriani, Paul (Fictitious character) -- Fiction; Fiction; Legal fiction (Literature); Thrillers (Fiction)